2010
DOI: 10.1002/j.2051-3909.2010.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographers' ability to perceive and classify abnormalities on mammographic images — results of a pilot project

Abstract: Purpose: The literature indicates that image interpretation as a developing role for radiographers is becoming more popular overseas. However, little is known about the ability of Australian radiographers to interpret radiographic images. The aim of this study is to provide pilot data to determine how well radiographers, without formal image interpretation training, can read mammograms. Methods: Twelve radiographers employed by the BreastScreen Queensland screening service were divided into two equal groups ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…6,[8][9][10][11][12] Other options to increase radiographer numbers may include making provisions for Assistant Practitioners, following the UK four tier model 13 or allowing male radiographers to perform mammograms in the currently female dominated BreastScreen setting. The Newcastle BreastScreen Service recruited radiographers from overseas (mainly the UK and Canada) between 1991 and 2004 due to a lack of available mammography trained workers in this country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[8][9][10][11][12] Other options to increase radiographer numbers may include making provisions for Assistant Practitioners, following the UK four tier model 13 or allowing male radiographers to perform mammograms in the currently female dominated BreastScreen setting. The Newcastle BreastScreen Service recruited radiographers from overseas (mainly the UK and Canada) between 1991 and 2004 due to a lack of available mammography trained workers in this country.…”
Section: Discussionmentioning
confidence: 99%
“…Of radiographers who are employed solely in BSA, 44% spend more than three-quarters (75%) of their working time performing screening mammograms, while 26% spend 100% in screening only roles (Table 3). From other duties performed within their BSA programme, the majority of radiographers undertook quality assurance duties (33) with relatively few radiographers undertaking training of staff (8) and breast ultrasound (7) ( Table 4).…”
Section: Working Practicesmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer in women worldwide 1 . Early detection is key to decreased morbidity and mortality with dedicated screening programmes available in many countries worldwide including, Australia, 2 the United States, 3 and the United Kingdom 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Radiographers as screen readers in Australia has been the recent focus of articles published in Th e Radiographer [1][2][3] and elsewhere. 4,5 Th is renewed interest prompts a review of the current situation in Australia together with considerations of a way forward.…”
mentioning
confidence: 99%
“…Th e accuracy of radiographer screen readers and the benefi ts they bring to screening programs have been emphasised in publications overseas. 6 Articles by Moran, et al 2,4 and Holt, et al 1 have demonstrated the potential for selected Australian radiographers with training to take on the role of screen readers. Th ese are encouraging results.…”
mentioning
confidence: 99%